Mental Health Status and Intelligence Level of Novices in The Phrapariyuttidham Schools Sing Buri Province - Serisathien, Prayuk; Ucharatna, Wacharee; Sonpugdee, Chariya (Journal of Health Science of Thailand, 2018)
TThe survey of mental health status and intelligence level of novices In The Phrapariyuttidhamschools Sing Buri province was aimed at observing existing mental health problems and applied inpromotion of mental health status, developing intelligence level, and emotional quotient (EQ) ofnovices. As such,it would enable them to be good in self-adjustment; to understand themselves aswell as others correctly and to handle stresses that they are facing in life. The study samples were 81novices aged not over 15 years and studying in Matthayom between level 1 and 2, in school year2008, at Mahavajiralongkorn Royal College 2, Pai Dum temple, Sing Buri province. The data col-lection method used was to let novices answer the questions in the classes and then a psychologistevaluated their IQ. Data was analyzed by descriptive statistics and presented in terms of percentage,mean, standard deviation, Pearson’s product moment correlation coefficient, and stepwise multipleregression analysis. The major findings were about 49.4 of novices were facing medium level ofstress, 22.2 were depressed, 51.9 had IQ over average level, and 51.9 had average level of EQ.Numbers of siblings, smoking, depression, and EQ were significantly related to stress with statisti-cal significance. The results showed that depression showed a positive relationship (r=0.36). Onthe other hand, numbers of siblings, smoking, and level of EQ indicated opposite relationships. Inaddition, the study found that EQ in self-control, self-motivation, self-decision making, and prob-lem solving, relationship, self-esteem, life satisfaction, peace in life provided opposite relationshipsto the stress. The component having most effects was “peace in life (r=0.37)”. The factors that couldcollectively predict the stress of novices were status of being depressed, level of EQ and smoking.The stress level of novices were about 23.6 which could be included as “prediction equation” as Y = 4.464+0.688X1-0.390X2-0.801X3